Xylazine, naloxone, and e‐cigarettes in recent FDA alerts. Issue 4 (20th January 2023) - Knopf, Alison
Abstract : This month the federal Food and Drug Administration (FDA) highlighted three topics needing urgent attention in the substance use disorder field: Xylazine contamination, over‐the‐counter naloxone availability, and marketing of e‐cigarettes.